Uptake and Intracellular Activity of Moxifloxacin in Human Neutrophils and Tissue-Cultured Epithelial Cells - Pascual, Alvaro (American Society for Microbiology, 1999)
The penetration by moxifloxacin of human neutrophils (polymorphonuclear leukocytes [PMN]) and tissue-cultured epithelial cells (McCoy cells) was evaluated by a fluorometric assay. At extracellular concentrations of 5 mg/liter, the cellular-to-extracellular concentration ratios (C/E) of moxifloxacin in PMN and McCoy cells were 10.9 ± 1.0 and 8.7 ± 1.0, respectively (20 min; 37°C). The uptake of moxifloxacin by PMN was rapid, reversible, nonsaturable (at extracellular concentrations ranging from 1 to 50 μg/ml), and not affected by cell viability. The uptake of moxifloxacin was affected by external pH and the environmental temperature. The incubation of PMN in the presence of sodium fluoride, sodium cyanide, and carbonyl cyanide m-chlorophenylhydrazone significantly decreased the C/E of this agent. Neither PMN stimulation nor phagocytosis of opsonized Staphylococcus aureus significantly affected the uptake of moxifloxacin by human PMN. This agent, at concentrations of 0.5, 1, and 5 mg/liter, induced a significant reduction in the survival of intracellular S. aureus in human PMN. In summary, moxifloxacin reaches much higher intracellular concentrations within phagocytic and nonphagocytic cells than extracellular ones, remaining active inside the neutrophils.